2017
DOI: 10.1038/cddiscovery.2016.101
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative real-time approach for discriminating apoptosis and necrosis

Abstract: Apoptosis and necrosis are the two major forms of cell death mechanisms. Both forms of cell death are involved in several physiological and pathological conditions and also in the elimination of cancer cells following successful chemotherapy. Large number of cellular and biochemical assays have evolved to determine apoptosis or necrosis for qualitative and quantitative purposes. A closer analysis of the assays and their performance reveal the difficulty in using any of these methods as a confirmatory approach,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…Apoptosis and necrosis are highly conserved cell death mechanisms involved in the elimination of cancer cells by anti-cancer agents [ 17 ]. Distinguishing specific cell death subtypes is highly important to develop antineoplastic or other therapeutic drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Apoptosis and necrosis are highly conserved cell death mechanisms involved in the elimination of cancer cells by anti-cancer agents [ 17 ]. Distinguishing specific cell death subtypes is highly important to develop antineoplastic or other therapeutic drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have found that myocardial cells have both necrotic and apoptotic forms during I/R in acute myocardial infarction, and apoptosis can be caused by acute myocardial infarction. 30,31 With the induction of external death signals, nucleated cells initiate their own internal gene expression and regulation through signal transduction pathways, leading to programmed process of cell death, which has a great effect…”
Section: Discussionmentioning
confidence: 99%
“…Many innovative approaches were ascertained in developing Green fluorescent protein (GFP) based sensors for signaling molecules such as calcium, reactive oxygen species (ROS), ATP, pH, cAMP [11] , [12] , [13] , [14] , [15] . Genetically encoded fluorescent probe based cell death tools were also described for toxicological studies [16] , [17] , [18] , [19] . We have described a high-throughput FRET-based method for caspase profiling [16] , [20] .…”
Section: Introductionmentioning
confidence: 99%
“…Genetically encoded fluorescent probe based cell death tools were also described for toxicological studies [16] , [17] , [18] , [19] . We have described a high-throughput FRET-based method for caspase profiling [16] , [20] . Intracellular generation of ROS and dysfunctional redox signaling have been attributed to the cytotoxic activity of various antitumor agents.…”
Section: Introductionmentioning
confidence: 99%